PENGEMBANGAN MODUL PEMBELAJARAN IPA TERPADU BERBASIS KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) PADA MATERI PESAWAT SEDERHANA KELAS VIII - Reviana Putri Febrianti; Indica Yona Okyranida; Dandan Luhur Saraswati (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2020)
The development of integrated science learning module based on Number Head Together (NHT) type cooperative learning model for grade VIII smp is research with research and development (R&D) method using addie model development concept (Analyze, Design, Develop, Implement, and Evaluate). This research resulted in an integrated science learning module based on a number head together (NHT) type cooperative learning model for grade VIII junior high school that is worthy of use based on validation of material experts, media experts, linguists and trials of students through limited and expanded trials, as well as trials of teachers as users. Based on the overall validation results of the three experts, namely materials, media, and language, an average score of 79% with the category "Good". While the results of limited trials obtained an average score of 80% with the category "Good". The results of the expanded trial obtained an average score of 79% with the category "Good" and the results of teacher trials as users obtained an average score of 90% with the category "Excellent". Based on 86 results, it can be concluded that integrated science learning module based on cooperative learning model type Number Head Together (NHT) for grade VIII junior high school is feasible to be used in school learning.